TRADISI MESBES BANGKE DARI BANJAR BURUAN,TAMPAK SIRING, GIANYAR, BALI - Ida Ayu Putu Sari; I Made Yudabakti (WIDYANATYA, 2022)
ABSTRACT Hinduism is one of the majority beliefs held by the people in Bali. Hinduism is a religion that has the oldest age and is the religion that was first recognized by humans. Hinduism originated in India, this religion is a contest between the religions of the Aryans and the Dravidians. The Aryans who came from Asia Tengah succeeded in urging the native Indians of the Dravina. There was an assimilation between the Aryans and the Dravidians which in turn gaverise to a generation called the Hinduism. The word Hindu comes from the word Sindhu which means river. Thisword refers to the Indus river which is a source of water for the life around it. Sources of Hindu teachings are found in the Veda scriptures (consisting of four books), Brahmans (an interpretations of the Veda), and Upanisads (containing the philosophical foundations of the relationship between human and God). Bali has many traditions. Tradition is a form of action that is repeated in the same way. The word "tradition" is taken from the Latin "Tradere" which means to transmit from generation to generation to be preserved. Tradition is generally known as a form of habit that has a series of ancient historical events. Each tradition was developed for some purpose, such as political goals or cultural goals over a period of time. In Bali, there is a very strong tradition, oneof which is the tradition in Banjar Buruan, Tampak Siring, Gianyar Bali, namely "Mesbes Bangke" whose tradition is quite extreme to do. The tradition of Mesbes Bangke Bali is not carried out all the time before the Ngaben ceremonyand this custom is only carried out on corpses who undergo a personal Ngabenceremony. ABSTRAK Agama Hindu merupakan salah satu kepercayaan mayoritas yang dianut oleh masyarakat di Bali. Agama Hindu merupakan agama yang memiliki usia paling tua dan merupakan agama yang pertama kali dikenal oleh manusia. Agama Hindu berasal dari India, agama ini merupakan gabungan antara bangsa Arya dan Dravida. Bangsa Arya yang datang dari Asia Tengah berhasil mendesak orang India asli Dravina. Ada asimilasi antara Arya dan Dravida yang pada gilirannya memunculkan generasi yang disebut Hindu. Kata Hindu berasal dari kata Sindhu yang berarti sungai. Kata ini merujuk pada sungai Indus yang merupakan sumber air bagi kehidupan di sekitarnya. Sumber ajaran Hindu ditemukan dalam kitab suci Weda (terdiri dari empat kitab), Brahman (sebuah interpretasi dari Weda), dan Upanisad (berisi landasan filosofis hubungan antara manusia dan Tuhan). Bali memiliki banyak tradisi. Tradisi adalah suatu bentuk tindakan yang diulang- ulang dengan cara yang sama. Kata “tradisi” diambil dari bahasa latin “Tradere” yang berarti mewariskan dari generasi ke generasi untuk dilestarikan. Tradisi secara umum dikenal sebagai suatu bentuk kebiasaan yang memiliki rangkaian peristiwa sejarah purbakala. Setiap tradisi dikembangkan untuk beberapa tujuan, seperti tujuan politik atau tujuan budaya selama periode waktu tertentu. Di Bali terdapat tradisi yang sangat kental salah satunya adalah tradisi di Banjar Buruan,Tampak Siring, Gianyar Bali yaitu “Mesbes Bangke” yang tradisinya cukup ekstrim untuk dilakukan. Tradisi Mesbes Bangke Bali tidak dilakukan setiap saat sebelum upacara Ngaben dan adat ini hanya dilakukan pada jenazah yang menjalani upacara ngaben pribadi